Posterior circulation collateral flow modifies the effect of thrombectomy on outcome in acute basilar artery occlusion. Issue 7 (August 2022) - Broocks, Gabriel; Faizy, Tobias D; Meyer, Lukas; Groffmann, Maximilian; Elsayed, Sarah; Kniep, Helge; Flottmann, Fabian; Bechstein, Matthias; Rusche, Thilo; Schön, Gerhard; Nawabi, Jawed; Sporns, Peter; et al.
Background: In basilar artery occlusion stroke, the impact of the collateral circulation on infarct progression in the context of endovascular treatment is yet poorly studied. Aim: This study investigates the impact of the posterior circulation collateral score (PCCS) on functional outcome according to the extent of early ischemic changes and treatment. We hypothesized that the presence of collaterals, quantified by the PCCS, mediates the effect of endovascular treatment on functional outcome in patients with acute basilar artery occlusion. Methods: In this multicenter observational study, patients with basilar artery occlusion and admission computed tomography were analyzed. At baseline, Posterior circulation Acute Stroke Prognosis Early Computed Tomography score (pcASPECTS) was assessed and PCCS was quantified using an established 10-point grading system. Logistic regression analyses were performed to identify factors associated with good functional outcome (modified Rankin Scale scores 0–2 at day 90). Results: A total of 151 patients were included, of which 112 patients (74%) underwent endovascular treatment. In patients with a better PCCS (>5), the rate of good outcome was significantly higher (55% vs. 11%; p = 0.001). After adjusting for PCCS, vessel recanalization was significantly associated with improved functional outcome (aOR: 4.53, 95%CI: 1.25–16.4, p = 0.02), while there was no association between recanalization status and outcome in univariable analysis. Patients with low pcASPECTS generally showed very poor outcomes (mean modified Rankin Scale score 5.3, 95%CI: 4.9–5.8). Conclusion: PCCS modified the effect of recanalization on functional outcome, particularly in patients with less pronounced ischemic changes in admission computed tomography. These results should be validated to improve patient selection for endovascular treatment in basilar artery occlusion, particularly in uncertain indications, or to triage patients at risk for very poor outcomes.